Food regulation and safety - Hillstrom, Kevin, 1963- (Detroit : Lucent Books, 2012)
'Each title in the series delves into some of the hottest nutrition and health topics being discussed today. The series also provides readers with tools for evaluating conflicting and ever-changing ideas about nutrition and health'--
Includes bibliographical references and index.
Keywords: Food -- Safety measures; Food contamination